2017
DOI: 10.1101/129049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gestational age at birth and risk of intellectual disability without a common genetic cause: findings from the Stockholm Youth Cohort

Abstract: Background: Preterm birth is linked to intellectual disability and there is evidence to suggest post-term

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Different results found in studies conducted Heuvelman et al (2017) in Stockholm, Sweden, who found that preterm birth makes it possible to increase the risk of mental retardation, special education needs, poor school performance and lower IQ in childhood and adulthood. Premature birth can also increase the risk of neurodevelopmental problem long term.…”
Section: Resultsmentioning
confidence: 62%
“…Different results found in studies conducted Heuvelman et al (2017) in Stockholm, Sweden, who found that preterm birth makes it possible to increase the risk of mental retardation, special education needs, poor school performance and lower IQ in childhood and adulthood. Premature birth can also increase the risk of neurodevelopmental problem long term.…”
Section: Resultsmentioning
confidence: 62%